Pendidikan Kewarganegaraan sebagai Strategi Counter Disinformation di Era Post-Truth: Citizenship Education as a Counter Disinformation Strategy in the Post-Truth Era - Ahmad Muhammad Mustain Nasoha; Zahra Dwi Pusparini; Hikma Paujia; Vera Dewi Saputri; Hanifa Anan (LITERA: Jurnal Ilmiah Mutidisiplin, 2025)
The development of digital technology has magnified the phenomenon of disinformation, giving birth to the post-truth era, where emotions and personal beliefs influence public opinion more strongly than objective facts, creating a flood of false information (hoaxes) that is difficult to distinguish from the truth. In this era, truth no longer relies on facts, but on subjective perspectives. Hoaxes and fake news are spread widely through social media, making it difficult for people to distinguish between valid news and what is not. To deal with this phenomenon, citizenship education must build moral intelligence and character in the nation's generation. By teaching values ​​such as critical and rational thinking, being responsible, being intelligent and making good use of information technology, citizenship education can help people become more aware and more selective in receiving information. Therefore, citizenship education must be an integral part of efforts to combat disinformation and hoaxes, as well as build the morals and character of a better generation of the nation.